2009
DOI: 10.1007/s11661-009-9982-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Cycling on Creep Behavior of Powder-Metallurgy-Processed and Hot-Rolled Al and Al-SiC Particulate Composites

Abstract: The tensile creep behavior of powder metallurgy (P/M)-processed and hot-rolled commercially pure Al and Al-5 or Al-10 vol pct SiC particulate composites has been evaluated after subjecting to 0, 2, and 8 thermal cycles between 500°C and 0°C with rapid quenching. The images of microstructures obtained using scanning and transmission electron microscopy as well as changes in the electrical resistivity, Young's modulus, and microhardness have been examined in the samples subjected to thermal cycling, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The similar behavior has been reported for glass particles reinforced Al-based composites [6,33]. As The significant increase in the mechanical strength of the composite compared to the pure aluminum arise from strengthening mechanisms due to the presence of micro sized reinforcement particles, including grain refinement strengthening [34], load transfer effect [34] and enhanced dislocation density induced by the difference in the coefficient of thermal expansion between the matrix and reinforcing particles [35,36]. Grain refinement of the composite matrix increases the strength according to the well-known Hall-Petch equation:…”
Section: Mechanical Properties 13supporting
confidence: 76%
“…The similar behavior has been reported for glass particles reinforced Al-based composites [6,33]. As The significant increase in the mechanical strength of the composite compared to the pure aluminum arise from strengthening mechanisms due to the presence of micro sized reinforcement particles, including grain refinement strengthening [34], load transfer effect [34] and enhanced dislocation density induced by the difference in the coefficient of thermal expansion between the matrix and reinforcing particles [35,36]. Grain refinement of the composite matrix increases the strength according to the well-known Hall-Petch equation:…”
Section: Mechanical Properties 13supporting
confidence: 76%
“…Also, the uniformity of the alumina particles has an important effect on the strength of the AMCs [38,45]. However, the hardness of the composites is expected to be higher with increasing the alumina content in the matrix, because of the dislocations generated due to the CTE mismatch between the alumina particles and the aluminum matrix [46,47]. The mean free path for dislocation movement is a function of the inter particle spacing.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The mean free path for dislocation movement is a function of the inter particle spacing. On the other hand, a high density of dislocations formed through the hot rolling process is expected to give rise to a high back stress, resisting further dislocation motion and causing dislocations to pile-up [6,46,48]. So, dislocations pile-up at metal/ceramic interfaces is caused by alumina particles.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Thermal cycling has been found to cause increase in microhardness near the particle-matrix interfaces of pure Al-TiC and Al-SiC composites, which could be attributed to strain hardening of the matrix by increase in dislocation density [28]. Further studies by Pal et al [29] have shown that subjecting the Al-SiC p composites to 2 or 8 thermal cycles leads to reduction in steady state creep rates along with significant increase in the time to rupture. Improvement in creep resistance has also been achieved by introducing line and point defects in the Al matrix by methods including prestressing [30] and quenching [31].…”
Section: Introductionmentioning
confidence: 99%